The Factors Underlying Lesbian Behavior and Their Implications for Guidance and Counseling Services - Febri Mulia Sri Ningsih; Yeni Karneli (Jurnal Neo Konseling, 2019)
Each individual basically requires the fulfillment of physical anda psychological needs wekk one of which is sexsual needs. But in fulfillment there are individuals who fulfill it in a deviant way. One of the deviant sexsual behaviors is homosexsual behavior. Homosexsual are individuals who have sexsual orientation of the sam sex. Women who have a sense of interest in women are called lesbians. Basically, an individual is born in a state of nature, and no one violates that nature, unless it is influenced by certain factors that cause the individual to leave the predetermined nature. This study aims to look at the factors underlying lesbian behavior seen from family, social environment, bad past experiences, and knowledge of religious norms and social norms prevailing in society. This study uses qualitative researsh methods in the form of case studies. The subject of this study consisted of two person. Types and sources of data used in this study include interviewing the subject, observing the subject’s behavior during the interview and teh subject’s social environment. The research instrument used was an interview and observation guide. In describing teh factors underliying the lesbian of money data analysis, three stages are used, including; (1) data reduction; (2) data display (data display); and (3) conclusion drawing/verification (conclusion drawing/verifiying), while the data analysis technique used in this study is a tehmatic analysis by transcribing interviews that have been verbalized. The results revealed that the faktors underlying the subject of being lesbian are as follows; (1) Factors of family background that are not harmonious, (2) Unfavorable social environment factors, (3) Faktors of poor past experience with the opposite sex.